The Motivational Make-Up of Workaholism and Work Engagement: A Longitudinal Study on Need Satisfaction, Motivation, and Heavy Work Investment - Taris, Toon W.; van Beek, Ilona; Schaufeli, Wilmar B. (Frontiers in Psychology, 2020)
Drawing on Ryan and Deci’s Self-Determination Theory, this study examines longitudinally how need satisfaction at work affects four forms of intrinsic and extrinsic work motivation and two types of heavy work investment (workaholism and work engagement). Using two-wave data from 314 Dutch employees, structural equation modelling supported our expectations that high need satisfaction was longitudinally associated with low levels of external and introjected regulation, and high levels of identified regulation and intrinsic motivation. Interestingly, none of these forms of regulation predicted later levels of work engagement and workaholism. Rather, high levels of work engagement predicted later high levels of intrinsic motivation and identified regulation, and high levels of workaholism predicted later low levels of intrinsic motivation and high levels of introjected regulation. Although this study did not support the expected longitudinal effects of motivation on the two types of heavy work investment examined in this study, it (a) underlined the important role of need satisfaction for motivation, (b) challenged previous ideas on the effects of motivation on workaholism and work engagement, and (c) revealed the different motivational correlates of work engagement and workaholism.